Enhancing Macroeconomic Resilience to Natural Disasters and Climate Change in the Small States of the Pacific - Cabezon, Ezequiel (IMF Working Papers; Working Paper ;, 2015)
Natural disasters and climate change are interrelated macro-critical issues affecting all Pacific small states to varying degrees. In addition to their devastating human costs, these events damage growth prospects and worsen countries' fiscal positions. This is the first cross-country IMF study assessing the impact of natural disasters on growth in the Pacific islands as a group. A panel VAR analysis suggests that, for damage and losses equivalent to 1 percent of GDP, growth drops by 0.7 percentage point in the year of the disaster. We also find that, during 1980-2014, trend growth was 0.7 percentage point lower than it would have been without natural disasters. The paper also discusses a multi-pillar framework to enhance resilience to natural disasters at the national, regional, and multilateral levels and the importance of enhancing countries' risk-management capacities. It highlights how this approach can provide a more strategic and less ad hoc framework for strengthening both ex ante and ex post resilience and what role the IMF can play.